The mitigative effects of Blautia producta 1009924 on DSS-induced intestinal inflammation - Chen, Yishu; Ma, Yan; Leng, Yang; Li, Xiaoling; Qin, Sishi; Li, Xiaoyan; Zhang, Zhao; Yu, Huajun (Frontiers in Microbiology, 2025)
IntroductionThe gut microbiota plays a crucial role in the treatment of inflammatory bowel disease (IBD). Recent studies have shown that the abundance of Blautia producta is associated with host inflammatory bowel disease (IBD), yet its specific mechanism of action remains to be further investigated.MethodsThe strain Blautia producta 1009924 (B. producta 1009924) was isolated from fresh fecal samples, and its biological characteristics and genomic features were analyzed. In this study, a zebrafish intestinal inflammation model was established by induction with 0.5% dextran sulfate sodium (DSS) for 72 h to evaluate the effect of B. producta 1009924 on alleviating intestinal inflammation.ResultsThis strain B. producta 1009924 is a strict anaerobe, forming circular, off-white colonies on BHI medium. It is Gram-positive, arranged in chains, and field emission scanning electron microscopy revealed abundant surface folds and pilus structures, along with excellent acid and bile salt tolerance. Whole-genome sequencing showed a total gene length of 6.05 Mb, a GC content of 45.72%, and 5,214 coding genes with no virulence genes. KEGG database annotation indicated that its gene functions are mainly enriched in metabolic pathways, environmental information processing, and genetic information processing, with abundant gene clusters involved in lipid metabolism and short-chain fatty acid (SCFA) metabolic pathways. Compared with the DSS-induced enteritis model group, B. producta 1009924 inhibited reactive oxygen species (ROS) production and neutrophil accumulation in zebrafish intestines. Histopathological analysis confirmed that it alleviated DSS-induced intestinal tissue damage, such as increasing goblet cell numbers and improving intestinal villus architecture. Real-time quantitative polymerase chain reaction (RT-qPCR) analysis demonstrated that B. producta 1009924 suppressed the activation of the TLR4/NF-κB signaling pathway by downregulating the expression of TLR4, MyD88, and NF-κB genes, thereby reducing the expression of pro-inflammatory factors (IL-6, IL-12) and the immune factor IL-10. Additionally, metabolomic analysis revealed that B. producta 1009924 regulated intestinal metabolism by increasing SCFA levels, including butyric acid and isovaleric acid.ConclusionBlautia producta 1009924 significantly alleviates DSS-induced intestinal inflammation in zebrafish by regulating ROS levels, inhibiting excessive immune and inflammatory responses, and improving SCFA metabolism, highlighting its potential as a candidate strain for IBD treatment.